Characterization and Stabilization of a New 64Cu-Labeled Anti-EGFR Antibody NCAB001 for the Early Detection of Pancreatic Cancer with Positron Emission Tomography - Hiroki Matsumoto; Chika Igarashi; Tomoko Tachibana; Fukiko Hihara; Atsuo Waki; Ming-Rong Zhang; Sei Yoshida; Kenichiro Naito; Hiroaki Kurihara; Makoto Ueno; Kimiteru Ito; Tatsuya Higashi; et al. (MDPI AG, 2021)
Early diagnosis of pancreatic cancer using current imaging modalities remains challenging. We have developed a new approach to identify tumor lesions ≥ 3 mm in the pancreas by positron emission tomography (PET) with a new intraperitoneally administered 64Cu-labeled anti-epidermal growth factor receptor (EGFR) antibody (encoded as NCAB001), called 64Cu-NCAB001 ipPET. Generally, in clinical research, a radiometal-antibody complex must be prepared immediately before use at the imaging site. To make 64Cu-NCAB001 ipPET available to daily clinical practices in a sustainable way, the NCAB001-chelator conjugate and 64Cu-NCAB001 must be characterized and stabilized. NCAB001 was manufactured under cGMP conditions. NCAB001 was conjugated with a bifunctional chelator (p-SCN-Bn-PCTA), and the antibody-chelator conjugate (PCTA-NCAB001) was characterized by LC/MS and ELISA. Thereafter, to effectively manufacture 64Cu-NCAB001, we developed a new formulation to stabilize PCTA-NCAB001 and 64Cu-NCAB001. An average of three PCTA chelators were conjugated per molecule of NCAB001. The relative binding potency of PCTA-NCAB001 was comparable to cetuximab. The formulation consisting of acetate buffer, glycine, and polysorbate-80 stabilized PCTA-NCAB001 for a year-long storage. Additionally, this formulation enabled the stabilization of 64Cu-NCAB001 for up to 24 h after radiolabeling with a sufficient radioactivity concentration for clinical use. These results may accelerate the future use of 64Cu-NCAB001 ipPET in clinical settings for the early diagnosis and treatment of pancreatic cancer.